2015
DOI: 10.1021/acsami.5b10183
|View full text |Cite
|
Sign up to set email alerts
|

Reversible and Irreversible Responses of Defect-Engineered Graphene-Based Electrolyte-Gated pH Sensors

Abstract: We have studied the role of defects in electrolyte-gated graphene mesh (GM) field-effect transistors (FETs) by introducing engineered edge defects in graphene (Gr) channels. Compared with Gr-FETs, GM-FETs were characterized as having large increments of Dirac point shift (∼30-100 mV/pH) that even sometimes exceeded the Nernst limit (59 mV/pH) by means of electrostatic gating of H(+) ions. This feature was attributed to the defect-mediated chemisorptions of H(+) ions to the graphene edge, as supported by Raman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 37 publications
1
32
0
1
Order By: Relevance
“…Disease-related small marker molecules like glucose [100], dopamine [87], urea [102], or environmental-related parameters such as 17β-estradiol [103], pH [104], heavy metal ions [105], or chlorine [106] have also be determined by GFETs. Selectivity can be achieved by using a differential measurement of two differently modified GFETs as it is illustrated in Fig.…”
Section: Field-effect Transistors and Chemiresistorsmentioning
confidence: 99%
“…Disease-related small marker molecules like glucose [100], dopamine [87], urea [102], or environmental-related parameters such as 17β-estradiol [103], pH [104], heavy metal ions [105], or chlorine [106] have also be determined by GFETs. Selectivity can be achieved by using a differential measurement of two differently modified GFETs as it is illustrated in Fig.…”
Section: Field-effect Transistors and Chemiresistorsmentioning
confidence: 99%
“…To investigate the effect of defects in graphene-based FET pH sensors, electrolyte-gated graphene-FET (Gr-FET) and graphene mesh–FET (GM-FET) devices have been tested [ 32 ]. Both sensors exhibit negative Dirac point shifts upon decreases in pH.…”
Section: Graphene Mesh Ph Sensorsmentioning
confidence: 99%
“…Furthermore, the irreversible response is believed to be caused by the direct adsorption of ions onto defects, which presumably involved strong chemisorption. It has been reported that H + ions were attached so strongly to the edge defects and have only been detached after high temperature annealing [ 32 ]. Such strong interactions were rarely reversed, and thus led to passivation of the defects upon repeated exposure to acidic solutions.…”
Section: Graphene Mesh Ph Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Поэтому особый интерес в последнее время вызывают интерфейсные эффекты, влияющие на электрические свойства графена [1][2][3][4][5][6][7][8]. В том числе, большое внимание направлено на создание и изучение сенсорных устройств, в которых исследуемые водные растворы находятся в интерфейсном контакте с графеном [1][2][3][4][5][6][9][10][11][12]. Интерфейсный эффект в структурах на основе выращенного в условиях вакуума четырехслойного графена, демонстрирующего дырочный тип проводимости, исследовался нами в работе [5] путем четырех контактных электрических измерений.…”
Section: Introductionunclassified